Clinical outcomes following total hip arthroplasty for bony ankylosed hips: a propensity score-matched analysis - Sakumo Kii; Ryo Takamatsu; Motoki Sonohata; Masaya Ueno; Toshihiro Nonaka; Masaru Kitajima; Masaaki Mawatari (BMC Musculoskeletal Disorders, 2025)
Abstract Background Total hip arthroplasty (THA) is one of the most effective treatments for hip arthritis. However, postoperative outcomes of THA in patients with bony ankylosed hips remain inconclusive. We aimed to examine the postoperative results of THAs for bony ankylosed hips using propensity score matching. Methods A propensity score was calculated using logistic regression analysis for a bony-ankylosed group (40 hips, 38 patients) and a non-ankylosed (control) group (829 hips, 729 patients). Patients were followed up for more than 10 years after primary THA. The propensity score used five covariates: age, sex, height, weight, and body mass index. Propensity matching was performed, with each bony ankylosed hip being matched to a non-ankylosed control hip. The clinical outcomes of the Japanese Orthopaedic Association (JOA) hip scores and complications were investigated. Results The propensity-matched population consisted of 40 bony ankylosed hips (38 patients) and 40 hips (40 patients) of matched controls. In both groups, the postoperative JOA hip scores at the last follow-up significantly improved compared to the preoperative scores. The JOA hip scores at the last follow-up for all components in the bony-ankylosed group were significantly lower than those in the control group. The number of hips with postoperative complications was significantly higher in the bony-ankylosed group than that in the control group. Conclusions THA for patients with bony ankylosed hips achieved positive results, including improved JOA hip scores; however, these scores were inferior to those observed in patients with non-ankylosed hips. This should be preoperatively communicated to patients with bony ankylosed hips who undergo THA.